Parallel Pandemics Illustrate the Need for One Health Solutions - Tucker, Claire; Fagre, Anna; Wittemyer, George; Webb, Tracy; Abworo, Edward Okoth; VandeWoude, Sue (Frontiers in Microbiology, 2021)
African Swine Fever (ASF) was reported in domestic pigs in China in 2018. This highly contagious viral infection with no effective vaccine reached pandemic proportions by 2019, substantially impacting protein availability in the same region where the COVID-19 pandemic subsequently emerged. We discuss the genesis, spread, and wide-reaching impacts of this epidemic in a vital livestock species, noting parallels and potential contributions to ignition of COVID-19. We speculate about impacts of these pandemics on global public health infrastructure and suggest intervention strategies using a cost: benefit approach for low-risk, massive-impact events. We note that substantive changes in how the world reacts to potential threats will be required to overcome catastrophes driven by climate change, food insecurity, lack of surveillance infrastructure, and other gaps. A One Health approach creating collaborative processes connecting expertise in human, animal, and environmental health is essential for combating future global health crises.